MOTIVASI BELAJAR SISWA BERDASARKAN KEMAMPUAN KONEKSI MATEMATIS DALAM MASALAH KONTEKSTUAL MATERIPERBANDINGAN DI SMP - Asni Hidayatullah; Yulis Jamiah; Bistari Bistari (Universitas Tanjungpura, 2019)
AbstractThis study aims to describe student learning motivation based on mathematical connection ability in contextual problems on comparative material in the Mujahidin Junior High School Pontianak. The research method used is descriptive method with data collection tools in the form of tests of mathematical connection ability, learning motivation questionnaire, and interviews. The research subjects observed were 6students of class VIII consisting of 2 students with high mathematical connection ability, 2 students with moderate mathematical connection ability, and 2 students with low mathematical connection ability. Motivation questionnaire results show students with high mathematical connection ability have high and medium learning motivation, students with moderate mathematical connection ability have moderate learning motivation, and students with low mathematical connection ability have low learning motivation. The results of the data analysis show that students who have high mathematical connection ability fulfill almost all observed motivation indicators, while students who have mathematical connection ability are only fulfilling some observed motivation indicators. As for students who have low mathematical connection skills do not meet all the motivational indicators observed.Keywords: Contextual Problems, Learning Motivation, Mathematical Connection Ability